ALKBH1: emerging biomarker and therapeutic target for cancer treatment - Ming Zhu Xiao; Jin Yin Fu; Le Tao Bo; Yi Dong Li; Zhong Wei Lin; Zhe Sheng Chen (Discover Oncology)
Abstract As neoplastic cells proliferate, disseminate, and infiltrate, they undergo substantial alterations in their epigenetic configuration. Among the pivotal enzymes implicated in this phenomenon is the AlkB family of demethylases, notably AlkB homolog 1 (ALKBH1), which demonstrates conspicuous upregulation across various malignancies. The heightened expression of ALKBH1 renders it a compelling candidate for the development of multifaceted anticancer modalities. Despite the commendable progress achieved by investigators in elucidating the perturbations associated with ALKBH1 in malignant tissues, a comprehensive mechanism remains elusive. The present study endeavors to address this lacuna by synthesizing recent advancements pertaining to ALKBH1's involvement in oncogenesis over the preceding decade. Therefore, this research not only furnishes novel insights but also establishes a foundation for prospective initiatives aimed at cancer prophylaxis and therapeutics that exploit epigenetic regulatory mechanisms.